Projekt Slovenščina na dlani - Ulčnik, Natalija (Slavia Centralis, 2020)
The author presents the project Slovenščina na dlani, which has been running since August 2017. The Faculty of Arts (FF), the Faculty of Electrical Engineering, Computer Science and Informatics (FERI) and the Faculty of Education (PEF) are participating in it.